Immunogenic Cell Death-Based Cancer Vaccines - Jin, Ming-Zhu; Wang, Xi-Peng (Frontiers in Immunology, 2021)
Cancer immunotherapy has achieved great advancement in the past decades. Whereas, its response is largely limited in immunologically cold tumors, in an urgent need to be solve. In recent years, an increasing number of studies have shown that inducing immunogenic cell deaths (ICDs) is an attractive approach to activate antitumor immunity. Upon specific stress, cancer cells undergo ICDs and dying cancer cells release danger associated molecular patterns (DAMPs), produce neoantigens and trigger adaptive immunity. ICDs exert a cancer vaccine-like effect and Inducement of ICDs mimics process of cancer vaccination. In this review, we propose a concept of ICD-based cancer vaccines and summarize sources of ICD-based cancer vaccines and their challenges, which may broaden the understandings of ICD and cancer vaccines in cancer immunotherapy.